EULAR randomised controlled trial of pulse cyclophosphamide and methylprednisolone versus continuous cyclophosphamide and prednisolone followed by azathioprine and prednisolone in lupus nephritis. Issue 5 (13th April 2004) - Yee, C-S; Gordon, C; Dostal, C; Petera, P; Dadoniene, J; Griffiths, B; Rozman, B; Isenberg, D A; Sturfelt, G; Nived, O; Turney, J H; Venalis, A; et al.
Abstract : Objective: To compare the efficacy and side effects of intermittent pulse cyclophosphamide plus methylprednisolone with continuous oral cyclophosphamide plus prednisolone, followed by azathioprine, in patients with proliferative glomerulonephritis caused by systemic lupus erythematosus (SLE). Methods: A multicentre randomised controlled trial was conducted between June 1992 and May 1996 involving eight European centres. All patients satisfied the American College of Rheumatology criteria for SLE and had biopsy proven proliferative lupus nephritis. All received corticosteroids in addition to cytotoxic drugs, as defined in the protocol, for two years. The trial was terminated after four years as recruitment was disappointing. Results: 32 SLE patients with lupus nephritis were recruited: 16 were randomised to intermittent pulse cyclophosphamide and 16 to continuous cyclophosphamide plus azathioprine. Mean duration of follow up was 3.7 years in the continuous group (range 0 to 5.6) and 3.3 years in the pulse group (range 0.25 to 6). Three patients were excluded from the pulse therapy group as they were later found to have pure mesangial glomerulonephritis. Two patients in the continuous therapy group developed end stage renal failure requiring dialysis, but none in the intermittent pulse therapy (p = 0.488; NS). There were similar numbers of side effects and withdrawals from treatment in both groups. There were three deaths: two in the intermittent pulse therapy group and one in the continuous therapy group. Conclusions: There was no statistically significant difference in efficacy and side effects between the two regimens. Infectious complications occurred commonly, so careful monitoring is required during treatment.